The Competencies That School-Leavers Should Possess in Order to Meet the Challenges of the 21st Century - Pellaud, Francine; Shankland, Rebecca; Blandenier, Gilles; Dubois, Laurent; Gey, Noémie; Massiot, Philippe; Gay, Philippe (Frontiers in Education, 2021)
The current state of the planet poses challenging ethical questions that shake up our emotions and values, thus making our choices and decisions more difficult. In order to grasp the many complex issues with which we are each confronted on a daily basis, education in sustainable development (ESD) advances competencies (UNESCO, 2017) that are rooted in both cognitive and socio-emotional processes. Although ESD is included in most school curricula, it is worth exploring what teachers perceive to be the real needs for these thinking tools, as well as how they value the development of these competencies in school. This research, which was carried out with pre-service and in-service teachers, answers these two questions. These initial results bring to light the interdisciplinary nature of the competencies considered necessary by the teaching profession, as well as the strengths and weaknesses of the current school system with regard to their development. This interdisciplinary approach leads us to a definition of what a competence is with regard to the specificity of the school context, and finally, to propose a typology. We have used this typology to compare the visions of the teaching staff with the competency frameworks proposed by the international bodies with the most influence in the Swiss school system, namely the World Economic Forum, the OECD, and UNESCO. Comparisons between these different elements open up perspectives on what tools could be proposed for assessing these competencies in schools in the long term.